Music and movement therapy improves quality of life and attention and associated electroencephalogram changes in patients with attention-deficit/hyperactivity disorder - Mei-Wen Lee; Ni-Jung Yang; Hin-Kiu Mok; Rei-Cheng Yang; Yi-Hung Chiu; Lung-Chang Lin (Elsevier, 2024)
Background: Attention-deficit/hyperactivity disorder (ADHD) is the most common neurobehavioral disorder. Treatments for ADHD include pharmacological and nonpharmacological therapy. However, pharmacological treatments have side effects such as poor appetite, sleep disturbance, and headache. Moreover, nonpharmacological treatments are not effective in ameliorating core symptoms and are time-consuming. Hence, developing an alternative and effective treatment without (or with fewer) side effects is crucial. Music therapy has long been used to treat numerous neurological diseases. Although listening to music is beneficial for mood and cognitive functions in patients with ADHD, research on the effects of music and movement therapy in children with ADHD is lacking. Methods: The present study investigated the effects of an 8-week music and movement intervention in 13 children with ADHD. The Pediatric Quality of Life Inventory (PedsQL) was used to evaluate changes in participants' quality of life. Conners' Kiddie Continuous Performance Test (K-CPT 2) and the Swanson, Nolan, and Pelham rating scale (SNAP-IV) were used to assess core symptoms. Electroencephalogram (EEG) recordings were analyzed to determine neurophysiological changes. Results: The results revealed that the participants' quality of life increased significantly after the 8-week intervention. Furthermore, the participants' hit reaction times in the block 1 and block 2 tests of K-CPT 2 decreased significantly after the intervention. EEG analysis demonstrated an increase in alpha power and Higuchi's fractal dimension and a decrease in delta power in certain EEG channels. Conclusion: Our music and movement intervention is a potential alternative and effective tool for ADHD treatment and it can significantly improve patients' quality of life and attention.